Solid electrolyte, preparation method thereof and all-solid-state battery comprising solid electrolyte
By doping fluorine on the surface of the sulfide-based solid electrolyte and forming a concentration gradient region, the problem of high reactivity to moisture is solved, and excellent moisture stability and high ionic conductivity are achieved.
Patent Information
- Application Number
- CN202380061922.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-31
- Filing Date
- 2023-10-31
- Publication Date
- 2025-03-28
AI Technical Summary
Sulfide solid electrolytes are highly reactive to moisture, causing reaction with moisture in the air to form harmful gas hydrogen sulfide, affecting its ionic conductivity and safety.
By doping fluorine on the surface of sulfide-based solid electrolyte particles, a fluorine-doped sulfide-based solid electrolyte is formed, and a concentration gradient region is formed on the surface, and the concentration of fluorine decreases from the surface to the inside. The electrolyte is heat treated with ammonium fluoride in a nitrogen atmosphere to form a hydrophobic surface and reduce reaction with moisture.
It realizes excellent moisture stability and low resistance of sulfide-based solid electrolytes, improves its ionic conductivity, making it suitable for large batteries with high capacity.
Smart Images

Figure CN119731828A_ABST
Abstract
Description
Technical Field
[0001] Cross-references to related applications
[0002] This application claims priority to Korean Patent Application No. 10-2022-0142618, filed on October 31, 2022, the disclosure of which is incorporated herein by reference. Technical Field
[0003] The present invention relates to a sulfide solid electrolyte having excellent moisture stability and ion conductivity, a preparation method thereof and an all-solid-state battery comprising the sulfide solid electrolyte. Background Art
[0004] All-solid-state batteries are batteries that replace the liquid electrolyte filled between the positive and negative electrodes of conventional lithium secondary batteries with solids. Among them, because it has a higher energy density than conventional batteries and is safe without the risk of explosion, it has attracted much attention as the next generation of batteries. The solid electrolyte used in all-solid-state batteries is a solid material that can conduct lithium ions in the battery, where it has a high ionic conductivity comparable to the ionic conductivity of the electrolyte currently used in lithium secondary batteries. The core materials that constitute the solid electrolyte include polymers, sulfides or oxides, but among them, sulfide-based solid electrolytes with high ductility and ionic conductivity are evaluated as suitable for preparing large-scale batteries with high capacity.
[0005] However, since the sulfide-based solid electrolyte has high reactivity to moisture, it has a problem of reacting with moisture in the air to generate harmful gas hydrogen sulfide. Therefore, there is a problem that the toxic hydrogen sulfide not only has an adverse effect on the safety of workers, but also reduces the ionic conductivity of the sulfide-based solid electrolyte itself.
[0006] In order to solve such problems of sulfide-based solid electrolytes, a method of doping aluminum (Al) and nitrogen (N) in a conventional electrolyte or forming a polymer coating has been studied, but there are problems that the improvement of moisture stability is not significant and the coating increases resistance.
[0007] Therefore, there is a need to develop a sulfide-based solid electrolyte that has excellent ion conductivity due to low resistance and excellent moisture stability.
[0008] [Prior art literature]
[0009] (Patent document) KR 2017-0050562 A Summary of the invention
[0010] Technical issues
[0011] One aspect of the present invention provides a solid electrolyte that, when included in a battery, has excellent moisture stability without adversely affecting the resistance of the battery.
[0012] In addition, another aspect of the present invention provides a method for preparing a solid electrolyte.
[0013] In addition, another aspect of the present invention provides an all-solid-state battery including a solid electrolyte.
[0014] Technical Solution
[0015] In order to accomplish the above tasks, the present invention provides a solid electrolyte, a preparation method thereof, and an all-solid-state battery comprising the solid electrolyte.
[0016] (1) The present invention provides a solid electrolyte, the solid electrolyte comprising:
[0017] a core portion including sulfide-based solid electrolyte particles; and
[0018] a surface portion formed on the core portion and including fluorine-doped sulfide-based solid electrolyte particles,
[0019] The surface portion includes a concentration gradient region in which a concentration of fluorine (F) atoms decreases in a direction from a surface of the surface portion toward the core portion.
[0020] (2) The present invention provides the solid electrolyte of (1) above, wherein the fluorine-doped sulfide-based solid electrolyte particles are represented by Chemical Formula 1:
[0021] [Chemical formula 1]
[0022] Li (12-x-b) BS( 6-x-a-b )X a F b Y x
[0023] Wherein, in Chemical Formula 1,
[0024] B is phosphorus (P), arsenic (As), germanium (Ge), gallium (Ga), antimony (Sb), silicon (Si), tin (Sn), aluminum (Al), indium (In), titanium (Ti), vanadium (V), niobium (Nb) or tantalum (Ta),
[0025] X is selenium (Se) or tellurium (Te),
[0026] Y is chlorine (Cl), bromine (Br), iodine (I), CN, OCN, SCN or N 3 ,and
[0027] x satisfies 0≤x≤2, a satisfies 0≤a≤2, b satisfies 0.1 <b≤1.0。
[0028] (3) The present invention provides the solid electrolyte of (1) or (2) above, wherein the fluorine-doped sulfide solid electrolyte particles are represented by Chemical Formula 1-1:
[0029] [Chemical formula 1-1]
[0030] Li 6 PS 5 Cl (1-b) F b
[0031] Among them, in chemical formula 1-1,
[0032] b satisfies 0.1 <b≤1.0。
[0033] (4) The present invention provides the solid electrolyte of any one of (1) to (3) above, wherein the sulfide-based solid electrolyte particles are argyrodite-type solid electrolytes.
[0034] (5) The present invention provides a solid electrolyte according to any one of (1) to (4) above, wherein the sulfide-based solid electrolyte particles are represented by Chemical Formula 2:
[0035] [Chemical formula 2]
[0036] Li (12-x) BS (6-x-a) X a Y x
[0037] Wherein, in Chemical Formula 2,
[0038] B is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta,
[0039] X is Se or Te,
[0040] Y is Cl, Br, I, CN, OCN, SCN or N 3 ,and
[0041] x satisfies 0≤x≤2, and a satisfies 0≤a≤2.
[0042] (6) The present invention provides a solid electrolyte according to any one of (1) to (5) above, wherein the concentration gradient region includes a region which is 30 nm or more and less than 1,200 nm away from the surface of the solid electrolyte in a direction from the surface of the solid electrolyte toward the core portion.
[0043] (7) The present invention provides the solid electrolyte of any one of (1) to (6) above, wherein the average particle size is in the range of 2 μm to 10 μm.
[0044] (8) The present invention provides a method for preparing a solid electrolyte, the method comprising the steps of heat treating sulfide solid electrolyte particles in the presence of ammonium fluoride in an inert gas atmosphere,
[0045] The amount of ammonium fluoride is 1 to 10 parts by weight based on 100 parts by weight of the sulfide-based solid electrolyte particles.
[0046] (9) The present invention provides the method of (8) above, wherein the sulfide-based solid electrolyte particles are argyrodite-type solid electrolytes.
[0047] (10) The present invention provides the method of (8) or (9) above, wherein the heat treatment is performed by sequentially performing a first heat treatment step and a second heat treatment step, wherein the first heat treatment step is performed at a temperature of 200°C to 300°C for 1 hour to 5 hours, and the second heat treatment step is performed at a temperature of 400°C to 600°C for 5 hours to 10 hours.
[0048] (11) The present invention provides an all-solid-state battery, the all-solid-state battery comprising:
[0049] positive electrode;
[0050] a negative electrode; and
[0051] The solid electrolyte according to any one of (1) to (7) above.
[0052] Beneficial Effects
[0053] Since the solid electrolyte according to the present invention includes a surface portion, which includes: sulfide solid electrolyte particles, in which hydrophobic fluorine is doped onto the surface of the sulfide solid electrolyte particles; and a concentration gradient region, in which the concentration of fluorine (F) atoms decreases in a direction from the surface toward the center of the solid electrolyte particles, not only is the moisture stability excellent, but also the ionic conductivity can be excellent due to the low resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The drawings attached to this specification illustrate specific examples of the present invention by way of example, and together with the specific embodiments of the present invention given below, enable a further understanding of the technical concept of the present invention. Therefore, the present invention should not be interpreted solely by the matters in these drawings.
[0055] Figure 1 is a scanning electron microscope (SEM) image of the solid electrolyte prepared in Example 1.
[0056] Figure 2 3 is a scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) image of the solid electrolyte prepared by Example 1, showing (a) a map of the sulfur (S) element, (b) a map of the phosphorus (P) element, (c) a map of the chlorine (Cl) element, and (d) a map of the fluorine (F) element.
[0057] Figure 3 3 is a graph showing the results of time-of-flight secondary ion mass spectrometry (TOF-SIMS) of the solid electrolyte prepared in Example 1. DETAILED DESCRIPTION
[0058] Hereinafter, the present invention will be described in more detail so that the present invention can be more clearly understood.
[0059] It should be understood that the words or terms used in this specification and the claims should not be interpreted as the meanings defined in commonly used dictionaries, and it should be further understood that based on the inventors can appropriately define the meanings of the words or terms in order to best explain the principles of the present invention, the words or terms should be interpreted as having meanings consistent with their meanings in the context of the relevant art and in the technical ideas of the present invention.
[0060] Definition of terms
[0061] The terms used herein are for the purpose of describing specific example embodiments only and are not intended to limit the present invention. In the present specification, unless otherwise specified, terms in the singular form may include plural forms.
[0062] In this specification, the term "concentration gradient" generally means a gradual change in the concentration of a solute, wherein the concentration gradient in the solid electrolyte of the present invention means a gradual change in the concentration of atomic components constituting the solid electrolyte.
[0063] The term "particle" in this specification means an object of a fine size constituting a corresponding material, such as elementary particles, atoms, molecules, and colloids.
[0064] In the present specification, it should be further understood that the terms "include", "comprises" or "has" specify the presence of stated features, numbers, steps, elements or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, elements or a combination thereof.
[0065] Measurement method
[0066] In this specification, the average particle size (D 50)" is measured using a particle size analyzer (PSA), wherein it is a particle size corresponding to 50% of the cumulative volume calculated from particles having a small particle size in a particle size distribution measured by a laser diffraction method.
[0067] Solid Electrolyte
[0068] The present invention provides a solid electrolyte having excellent ion conductivity and excellent moisture stability by including a surface portion including fluorine-doped sulfide-based solid electrolyte particles and a concentration gradient region on the surface of the sulfide-based solid electrolyte particles.
[0069] A solid electrolyte according to one embodiment of the present invention is characterized in that the solid electrolyte comprises:
[0070] a core portion including sulfide-based solid electrolyte particles; and
[0071] a surface portion formed on the core portion and including fluorine-doped sulfide-based solid electrolyte particles,
[0072] The surface portion includes a concentration gradient region in which a concentration of fluorine (F) atoms decreases in a direction from a surface of the surface portion toward the core portion.
[0073] Sulfide-based solid electrolytes react with moisture in the air to generate hydrogen sulfide gas, which not only reduces ion conductivity but also has an adverse effect on safety due to the toxicity of hydrogen sulfide gas.
[0074] Therefore, a method of doping aluminum (Al) and nitrogen (N) in a sulfide solid electrolyte or forming a polymer coating on the surface has been studied, but the improvement in moisture stability is not significant. In addition, since the sulfide solid electrolyte particles have a hydrophobic surface, it may be difficult to form a polymer coating containing a styrene-butadiene copolymer or an acrylonitrile-butadiene copolymer on the surface. Therefore, a method of forming a hydrophilic oxide buffer layer has been considered to help form a polymer coating, but the problem is that the resistance increases, and due to poor ductility, the hydrophilic oxide buffer layer is easily destroyed during the formation of the polymer coating.
[0075] As another example, a method of forming an oxide coating by oxidizing the surface of a sulfide-based solid electrolyte has been studied, in which moisture stability is improved, but there is a problem of poor ion conductivity due to an increase in resistance caused by the oxide coating.
[0076] However, since the solid electrolyte of the present invention includes a surface portion having a concentration gradient region by forming fluorine-doped sulfide solid electrolyte particles, wherein fluorine (F) replaces the sulfur (S) sites of the sulfide solid electrolyte to specific regions on the surface of the sulfide solid electrolyte particles by heat treating the sulfide solid electrolyte particles with ammonium fluoride adjusted to a specific amount in a nitrogen atmosphere, when the solid electrolyte is exposed to air, moisture stability and ionic conductivity can be excellent by effectively preventing reaction with moisture.
[0077] Specifically, the sulfide-based solid electrolyte particles may be a sulfide-based solid electrolyte containing lithium (Li), phosphorus (P), and S, and may be an argyrodite-type solid electrolyte in terms of high ion conductivity and low reactivity with a lithium negative electrode.
[0078] More specifically, the sulfide-based solid electrolyte particles may be represented by Chemical Formula 2 below.
[0079] [Chemical formula 2]
[0080] Li (12-x) BS (6-x-a) X a Y x
[0081] In chemical formula 2,
[0082] B is phosphorus (P), arsenic (As), germanium (Ge), gallium (Ga), antimony (Sb), silicon (Si), tin (Sn), aluminum (Al), indium (In), titanium (Ti), vanadium (V), niobium (Nb) or tantalum (Ta),
[0083] X is selenium (Se) or tellurium (Te),
[0084] Y is chlorine (Cl), bromine (Br), iodine (I), CN, OCN, SCN or N 3 ,and
[0085] x satisfies 0≤x≤2, and a satisfies 0≤a≤2.
[0086] As another example, for the sulfide-based solid electrolyte particles having Chemical Formula 2, B may be P, As, or Ga, X may be Se, and Y may be Cl, Br, or I.
[0087] For example, the sulfide-based solid electrolyte particles may be represented by the following Chemical Formula 2-1, Chemical Formula 2-2, or Chemical Formula 2-3.
[0088] [Chemical formula 2-1]
[0089] Li 6 PS 5 Z
[0090] In Chemical Formula 2-1, Z may be Cl, Br or I.
[0091] [Chemical formula 2-2]
[0092] Li 6 BS 5-a X a Y
[0093] In chemical formula 2-2,
[0094] B is P, As or Sb, X is Se or Te, and Y is Se, Br, I, CN, OCN, SCN or N 3 , 0≤a≤2.
[0095] [Chemical formula 2-3]
[0096] Li 7 BS 6-a X a
[0097] In chemical formula 2-3,
[0098] B is P, As or Sb, X is Se or Te, 0≤a≤2.
[0099] The surface portion includes fluorine-doped sulfide-based solid electrolyte particles, and includes a concentration gradient region in which the concentration of F atoms decreases in a direction from a surface of the surface portion toward the core portion.
[0100] Specifically, the surface portion is formed by heat treating sulfide solid electrolyte particles with ammonium fluoride in a nitrogen atmosphere to fluorinate the sulfide solid electrolyte to a predetermined area on the surface of the particles, wherein, since the sulfur (S) on the core portion of the sulfide solid electrolyte particles is replaced by fluorine (F), and the amount of replaced fluorine decreases in the direction from the surface to the inside of the core portion, the surface portion can have a concentration gradient region of F atoms while including fluorine-doped sulfide solid electrolyte particles.
[0101] The fluorine-doped sulfide solid electrolyte particles at the surface are those particles of sulfide solid electrolyte particles doped with fluorine, wherein the fluorine-doped sulfide solid electrolyte particles can be those particles in which a portion of the sulfur in the sulfide solid electrolyte particles is replaced with fluorine, and can be specifically represented by the following Chemical Formula 1.
[0102] [Chemical formula 1]
[0103] Li (12-x-b) BS( 6-x-a-b )X a F b Yx
[0104] In Chemical Formula 1,
[0105] B is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta,
[0106] X is Se or Te,
[0107] Y is Cl, Br, I, CN, OCN, SCN or N 3 ,and
[0108] x satisfies 0≤x≤2, a satisfies 0≤a≤2, b satisfies 0.1 <b≤1.0。
[0109] More specifically, the fluorine-doped sulfide-based solid electrolyte particles may be represented by the following Chemical Formula 1-1.
[0110] [Chemical formula 1-1]
[0111] Li 6 PS 5 Cl (1-b) F b
[0112] In Chemical Formula 1-1,
[0113] b satisfies 0.1 <b≤1.0。
[0114] In addition, the concentration gradient region of the surface portion may include a region that is 30 nm or more to less than 1,200 nm away from the surface of the surface portion in the direction from the surface of the surface portion toward the core portion, and may specifically include a region within the range of 30 nm to 1,000 nm, 100 nm to 1,000 nm, or 200 nm to 800 nm from the surface of the surface portion. If the concentration gradient region is within the above range, the reaction with moisture can be effectively blocked when exposed to air, and therefore, moisture stability and ionic conductivity can be excellent. In addition, in terms of obtaining a balancing effect of excellent ionic conductivity and effectively blocking the reaction with moisture, it may be more desirable that the concentration gradient region does not exceed the above range.
[0115] In addition, the solid electrolyte according to one embodiment of the present invention may have an average particle size of 2 μm to 10 μm or 2 μm to 5 μm, wherein if the average particle size is less than 2 μm, an electrolyte interface may be excessively formed to increase resistance, and if the average particle size is greater than 10 μm, excessive pores may be formed to increase resistance.
[0116] Method for preparing solid electrolyte
[0117] The present invention provides a method for preparing the solid electrolyte.
[0118] The method for preparing a solid electrolyte according to one embodiment of the present invention is characterized in that the method includes the step of heat-treating sulfide-based solid electrolyte particles in the presence of ammonium fluoride in a nitrogen atmosphere,
[0119] The amount of ammonium fluoride is 1 to 10 parts by weight based on 100 parts by weight of the sulfide-based solid electrolyte particles.
[0120] The heat treatment is a step of forming a surface portion on the surface of the sulfide-based solid electrolyte particle, wherein it can be performed by preparing the sulfide-based solid electrolyte particle and heat-treating the sulfide-based solid electrolyte particle in the presence of ammonium fluoride in a nitrogen atmosphere.
[0121] In this case, the amount of ammonium fluoride used can be 1 to 10 parts by weight, specifically 1 to 5 parts by weight or 1 to 3 parts by weight, based on 100 parts by weight of the sulfide solid electrolyte particles, and in this case, a surface portion having the above-mentioned concentration gradient region can be formed.
[0122] In addition, the heat treatment is performed by sequentially performing a first heat treatment step and a second heat treatment step, wherein the first heat treatment step can be performed at a temperature of 200°C to 300°C for 1 hour to 5 hours, and the second heat treatment step can be performed at a temperature of 400°C to 600°C for 5 hours to 10 hours.
[0123] In one embodiment of the present invention, the sulfide solid electrolyte can be prepared and used by a method generally known in the art, or can be purchased and used, and in the case of preparation and use, for example, it can be prepared by dissolving lithium sulfide, other sulfide raw materials and halogen compounds in a solvent to obtain a precursor solution, and drying and heat-treating the precursor solution, or can be prepared by grinding lithium sulfide, other sulfide raw materials and halogen compounds in a powder state to mix them, and heat-treating the mixture.
[0124] In this case, the lithium sulfide may be lithium sulfide (Li 2 S), other sulfide raw materials can be phosphosulfide, such as P 2 S 3 , P 2 S 5 , P 4 S 3 , P 4 S 5 and P 4 S 10 , specifically phosphorus pentasulfide (P2 S 5 ). In addition, the sulfide-based raw material may further include a substitution element, and in this case, the substitution element may be As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, Ta, Se and / or Te.
[0125] In addition, the halogen compound may be lithium bromide, lithium chloride, lithium iodide, and combinations thereof.
[0126] All-solid-state battery
[0127] The present invention provides an all-solid-state battery comprising the solid electrolyte.
[0128] Specifically, the all-solid-state battery includes:
[0129] A positive electrode, the positive electrode comprising a positive electrode active material;
[0130] a negative electrode, the negative electrode comprising a negative electrode active material; and
[0131] A solid electrolyte layer is provided between the positive electrode and the negative electrode, wherein the solid electrolyte layer includes the solid electrolyte according to the present invention.
[0132] Since the all-solid-state battery according to the present invention has a small amount of reduction in ion conductivity caused by moisture, the initial efficiency, life characteristics, and output characteristics of the battery may be excellent.
[0133] In this case, the all-solid-state battery of the present invention can be prepared according to a typical method known in the art. For example, the all-solid-state battery of the present invention can be prepared by stacking and pressing so that a solid electrolyte layer exists between the positive electrode and the negative electrode.
[0134] positive electrode
[0135] The positive electrode may be prepared by coating a positive electrode current collector with a positive electrode slurry including a positive electrode active material, a binder, a conductive material, and a solvent.
[0136] There is no particular limitation on the positive electrode current collector as long as it has conductivity without causing adverse chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, fired carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc. can be used. In addition, fine concavoconvexity can be formed on its surface to improve the bonding strength with the positive electrode active material, and the positive electrode current collector can be used in various shapes, such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.
[0137] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium, and the positive electrode active material may specifically include lithium metal oxides containing lithium and at least one metal such as cobalt, manganese, nickel or aluminum. More specifically, the lithium metal oxides may include lithium manganese oxides (e.g., LiMnO 2 , LiMn 2 O 4 etc.), lithium cobalt oxides (e.g., LiCoO 2 etc.), lithium nickel oxides (e.g., LiNiO 2 etc.), lithium nickel manganese oxides (e.g., LiNi 1-Y Mn Y O 2 (where 0 < Y < 1), LiMn 2-Z Ni z O 4 (where 0 < Z < 2) etc.), lithium nickel cobalt oxides (e.g., LiNi 1-Y1 Co Y1 O 2 (where 0 < Y1 < 1) etc.), lithium manganese cobalt oxides (e.g., LiCo 1-Y2 Mn Y2 O 2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O 4 (where 0 < Z1 < 2) etc.), lithium nickel manganese cobalt oxides (e.g., Li(Ni p Co q Mn r1 )O 2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1 and p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O 4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2 and p1 + q1 + r2 = 2) etc.), or lithium nickel cobalt transition metal (M) oxides (e.g., Li(Ni p2 Co q2 Mn r3 M S2 )O 2 (where M is selected from Al, iron (Fe), V, chromium (Cr), Ti, Ta, magnesium (Mg) and molybdenum (Mo), and p2, q2, r3 and S2 are the atomic fractions of the respective independent elements, where 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < S2 < 1, and p2 + q2 + r3 + S2 = 1) etc.), and may include any one of them or a mixture of two or more thereof.
[0138] Among these materials, lithium metal oxide may be LiCoO in terms of improvement of battery capacity characteristics and stability. 2 、LiMnO 2 、LiNiO 2 , lithium nickel manganese cobalt oxide (e.g., Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 ) 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 and Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 etc.) or lithium nickel cobalt aluminum oxide (e.g., LiNi 0.8 Co 0.15 Al 0.05 O 2 Considering the significant improvement effect brought about by controlling the type and content ratio of the components constituting the lithium composite metal oxide, the lithium composite metal oxide may be Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.5 Mn 0.3 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 and Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 , and any one thereof or a mixture of two or more thereof may be used.
[0139] The content of the positive electrode active material may be 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, based on the total weight of the solid matter excluding the solvent in the positive electrode slurry.
[0140] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.
[0141] The content of the binder may generally be 1 to 20 wt %, preferably 1 to 15 wt %, more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the slurry for the positive electrode.
[0142] The conductive material is a component that further improves the conductivity of the positive electrode active material.
[0143] There is no particular limitation on the conductive material as long as it has conductivity and does not cause adverse chemical changes in the battery. For example, conductive materials such as graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black or thermal black; conductive fibers such as carbon fibers or metal fibers; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides such as titanium oxide; or polyphenylene derivatives can be used.
[0144] The content of the conductive material may generally be 1 to 20 wt %, preferably 1 to 15 wt %, more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the slurry for the positive electrode.
[0145] The solvent may include an organic solvent, such as N-methyl-2-pyrrolidone (NMP), and may be used in an amount that obtains a desired viscosity when including a positive electrode active material and an optional binder and a conductive material. For example, the content of the solvent may be such that the concentration of the solids including the positive electrode active material and the optional binder and conductive material is in the range of 50% by weight to 95% by weight, preferably 70% by weight to 95% by weight, and more preferably 70% by weight to 90% by weight.
[0146] negative electrode
[0147] For example, the negative electrode may be prepared by coating a negative electrode slurry including a negative electrode active material, a binder, a conductive material, and a solvent on a negative electrode collector, or a graphite electrode formed of carbon (C) or a metal itself may be used as the negative electrode.
[0148] For example, in the case where the negative electrode is prepared by coating a negative electrode slurry on a negative electrode collector, the thickness of the negative electrode collector is generally 3 μm to 500 μm. There is no particular limitation on the negative electrode collector as long as it has high conductivity and does not cause adverse chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. can be used. In addition, similar to the positive electrode collector, the negative electrode collector can have fine surface irregularities to improve the bonding strength with the negative electrode active material, and the negative electrode collector can be used in different shapes, such as films, sheets, foils, nets, porous bodies, foams, non-woven fabrics, etc.
[0149] The negative electrode active material may include at least one negative electrode active material selected from the following: natural graphite, artificial graphite, carbonaceous material; lithium-containing titanium composite oxide (LTO), Si, SiO x , metal (Me) such as Sn, Li, zinc (Zn), Mg, cadmium (Cd), cerium (Ce), Ni or Fe; alloy composed of metal (Me); oxide (MeO x ); and a composite of a metal (Me) and carbon. As the negative electrode active material, specifically, silicon (Si), silicon oxide (SiO x ) or silicon-based negative electrode active materials of silicon alloys. In this case, since a thin and stable SEI layer containing siloxane bonds is formed, the high temperature stability and life characteristics of the battery can be further improved.
[0150] The content of the negative electrode active material may be 60 to 99 wt %, preferably 70 to 99 wt %, and more preferably 80 to 98 wt %, based on the total weight of solids excluding the solvent in the negative electrode slurry.
[0151] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.
[0152] The content of the binder may generally be 1 to 20 wt %, preferably 1 to 15 wt %, more preferably 1 to 10 wt %, based on the total weight of solids excluding the solvent in the slurry for the negative electrode.
[0153] The conductive material is a component that further improves the conductivity of the negative electrode active material. There is no particular limitation on the conductive material, as long as it has conductivity and does not cause adverse chemical changes in the battery, for example, conductive materials such as graphite, such as natural graphite or artificial graphite; carbon black, such as acetylene black, ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers or metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.
[0154] The content of the conductive material may be 1 to 20 wt %, preferably 1 to 15 wt %, and more preferably 1 to 10 wt %, based on the total weight of the solid matter excluding the solvent in the negative electrode slurry.
[0155] The solvent may include non-polar solvents such as toluene and xylene, and may be used in an amount to obtain a desired viscosity when including the negative electrode active material and optional binder and conductive material. For example, the content of the solvent may be such that the concentration of the solids including the negative electrode active material and optional binder and conductive material is in the range of 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %.
[0156] In the case of using the metal itself as the negative electrode, the negative electrode can be the metal film itself, or can be prepared by physically combining, rolling or depositing the metal on the negative electrode current collector. As a deposition method, an electrodeposition method or a chemical vapor deposition method of the metal can be used.
[0157] For example, the metal film itself or the metal to be bonded / rolled / deposited on the negative electrode current collector may include one metal or an alloy of two metals selected from lithium (Li), nickel (Ni), tin (Sn), copper (Cu) and indium (In).
[0158] Solid electrolyte layer
[0159] The solid electrolyte layer may further include a binder in addition to the solid electrolyte according to the present invention.
[0160] The binder is a component that helps to bind the conductive material, the active material and the current collector. Examples of the binder may be polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber, sulfonated ethylene propylene diene monomer rubber, styrene-butadiene rubber, fluororubber or various copolymers thereof.
[0161] The content of the binder may be generally 1 wt % to 20 wt %, preferably 1 wt % to 15 wt %, more preferably 1 wt % to 10 wt %, based on the total weight of the solid electrolyte layer.
[0162] The present invention provides a battery module including an all-solid-state battery as a unit cell, and can provide a battery pack including the battery module. Since the battery module and the battery pack include secondary batteries with high capacity, high rate performance and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles and power storage systems.
[0163] Hereinafter, preferred examples will be provided to better understand the present invention. It will be apparent to those skilled in the art that these examples are provided only to illustrate the present invention, and various modifications and changes may be made within the scope and technical spirit of the present invention. Such modifications and changes fall within the scope of the claims included herein.
[0164] Example 1
[0165] Li was milled 2 S.P. 2 S 5 and LiCl in a molar ratio of 5:1:2 and heat treated at 550 °C for 10 h to prepare a sulfide-based solid electrolyte (Li 6 PS 5 Cl).
[0166] While nitrogen was flowing, 10 mg NH 4 In the presence of F, 1 g of Li 6 PS 5 Cl was heat-treated at 250° C. for 3 hours and then at 550° C. for 10 hours, thereby preparing a solid electrolyte including a sulfide-based solid electrolyte core portion and a surface portion having a fluorine concentration gradient.
[0167] Example 2
[0168] A solid electrolyte including a sulfide-based solid electrolyte core portion and a surface portion having a fluorine concentration gradient was prepared in the same manner as in Example 1, except that 1 g of Li 6 PS 5 Cl in 20 mg NH 4 Heat treatment is carried out in the presence of F.
[0169] Example 3
[0170] A solid electrolyte including a sulfide-based solid electrolyte core portion and a surface portion having a fluorine concentration gradient was prepared in the same manner as in Example 1, except that 1 g of Li 6 PS 5 Cl in 30 mg NH 4 Heat treatment is carried out in the presence of F.
[0171] Comparative Example 1
[0172] Li was milled 2 S.P. 2 S 5 and LiCl in a molar ratio of 5:1:2 and heat treated at 550 °C for 10 h to prepare Li 6 PS 5 Cl as sulfide-based solid electrolyte.
[0173] Comparative Example 2
[0174] Li was milled 2 S.P. 2 S 5 and LiCl in a molar ratio of 5:1:2 and heat treated at 550 °C for 10 h to prepare a sulfide-based solid electrolyte (Li 6 PS 5 Cl).
[0175] While nitrogen and oxygen were flowing at a volume ratio of 9:1, 1 g of Li 6 PS 5 Cl was heat-treated at 250° C. for 3 hours, thereby preparing a solid electrolyte having an oxide coating layer formed thereon.
[0176] Comparative Example 3
[0177] A solid electrolyte having fluorine present throughout the particles was prepared in the same manner as in Example 1, except that in Example 1, 1 g of Li 6 PS 5 Cl in 1 g NH 4 Heat treatment is carried out in the presence of F.
[0178] Experimental Example 1
[0179] The surface composition of the solid electrolyte prepared in Example 1 was analyzed by SEM and SEM-EDS mapping analysis and TOF-SIMS analysis, and the results are presented in Figure 1 and Figure 2 middle.
[0180] In addition, the concentration gradient of fluorine element on the surface of the solid electrolyte prepared in Example 1 was analyzed, and the results showed that Figure 3 The results of the surface fluorine element concentration gradient analysis were expressed as relative intensity using Comparative Example 1 as a control group.
[0181] The composition and concentration distribution were obtained by TOF-SIMS and SEM analysis.
[0182] TOF-SIMS (Time of Flight - Secondary Ion Mass Spectrometry) analysis was performed using a TOF-SIMS 5 (ION-TOF, Münster, Germany) instrument under the following conditions.
[0183] Primary ion beam: Bi 1
[0184] Primary beam voltage: 30 KeV
[0185] Primary beam current: 1.0 pA
[0186] Analysis area: 150 μm × 150 μm (surface × depth)
[0187] Polarity: Negative mode
[0188] Sputtering beam: Cs +
[0189] Sputtering beam voltage / current: 2 KeV / 134 nA
[0190] Sputtering area: 500 μm×500 μm
[0191] SEM and SEM-EDS analyses were performed using a JEOL-7800F instrument by setting the accelerating voltage to 15 kV. Sampling was performed in an argon-filled glove box.
[0192] according to Figure 1 and Figure 2 , it can be confirmed that F exists on the surface of the solid electrolyte of Example 1, and according to Figure 3 , the solid electrolyte of Example 1 has a concentration gradient region in which F decreases in the direction from the surface toward the core.
[0193] Experimental Example 2
[0194] The moisture stability and ion conductivity of the solid electrolytes of the embodiment and the comparative example were analyzed in a comparative manner. The results are presented in Table 1 below.
[0195] (1) Moisture stability
[0196] The moisture stability was confirmed by measuring the amount of hydrogen sulfide generated when the solid electrolyte was exposed to air, wherein 100 mg of each solid electrolyte was placed in an airtight container equipped with a thermohygrometer and a hydrogen sulfide gas concentration meter and exposed to air at room temperature (23±5°C) and a relative humidity (RH) of 40% for 30 minutes, and the amount of hydrogen sulfide generated (cm 3 / g, the amount of hydrogen sulfide generated per 1 g of electrolyte).
[0197] (2) Ionic conductivity
[0198] In order to confirm the lithium ion conductivity of each solid electrolyte, an alternating current impedance analysis was performed at room temperature.
[0199] 0.15 g of each solid electrolyte was loaded into a lithium ion conductivity measurement jig, and a pressure of several hundred MPa was applied to prepare pellets. The lithium ion conductivity measurement jig containing the pelletized solid electrolyte was placed in a room with constant temperature and humidity, and then left to stand at room temperature for 40 minutes. Thereafter, an alternating potential of 100 mV was applied, and a frequency sweep from 1,000 Hz to 1 MHz was performed to obtain impedance.
[0200]
[0201] As shown in Table 1, it was confirmed that the solid electrolytes of Examples 1 to 3 had a low ion conductivity reduction rate of less than 5% and had an effect of significantly reducing the amount of generated hydrogen sulfide to 50% to 83% compared with Comparative Example 1. In contrast, for the solid electrolyte of Comparative Example 2 having an oxide coating layer, a high reduction rate in which the ion conductivity reduction rate was more than twice was exhibited, while the effect of reducing the amount of generated hydrogen sulfide was significantly lower than that of Examples 1 to 3.
[0202] In addition, for the solid electrolyte of Comparative Example 3 in which fluorine exists up to the core, the amount of hydrogen sulfide generated is reduced compared with those solid electrolytes in the embodiments, but since the ion conductivity reduction rate is about 4 to 9 times larger than that in the embodiments, it fails to show balanced excellence in terms of moisture stability and ion conductivity.
[0203] Through the above results, since the solid electrolyte according to the present invention includes a surface portion, which includes hydrophobic fluorine-doped sulfide solid electrolyte particles on the surface of the sulfide solid electrolyte particles, and includes a concentration gradient region in which the concentration of F atoms decreases in the direction from the surface toward the center of the solid electrolyte particles, the generation of hydrogen sulfide is significantly suppressed when exposed to moisture, and at the same time, it has excellent ionic conductivity corresponding to the sulfide solid electrolyte whose surface is not treated in any way, thereby confirming that it has an excellent moisture stability effect.
Claims
1. A solid electrolyte, comprising: a core portion including sulfide-based solid electrolyte particles; and a surface portion formed on the core portion and including fluorine-doped sulfide-based solid electrolyte particles, The surface portion includes a concentration gradient region in which the concentration of F atoms decreases in a direction from a surface of the surface portion toward the core portion.
2. The solid electrolyte according to claim 1, wherein the fluorine-doped sulfide-based solid electrolyte particles are represented by Chemical Formula 1: [Chemical formula 1] Li (12-x-b) BS( 6-x-a-b )X a F b Y x in, In Chemical Formula 1, B is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X is Se or Te, Y is Cl, Br, I, CN, OCN, SCN or N3, and x satisfies 0≤x≤2, a satisfies 0≤a≤2, b satisfies 0.1 <b≤1.0。 3. The solid electrolyte according to claim 1, wherein the fluorine-doped sulfide-based solid electrolyte particles are represented by Chemical Formula 1-1: [Chemical formula 1-1] Li6PS5Cl (1-b) F b in, In Chemical Formula 1-1, b satisfies 0.1 <b≤1.0。 4 . The solid electrolyte according to claim 1 , wherein the sulfide-based solid electrolyte particles are argyrodite-type solid electrolytes.
5. The solid electrolyte according to claim 1, wherein the sulfide-based solid electrolyte particles are represented by Chemical Formula 2: [Chemical formula 2] Li (12-x) B.S. (6-x-a) X a Y x in, In chemical formula 2, B is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta, X is Se or Te, Y is Cl, Br, I, CN, OCN, SCN or N3, and x satisfies 0≤x≤2, and a satisfies 0≤a≤2. 6 . The solid electrolyte according to claim 1 , wherein the concentration gradient region includes a region that is 30 nm or more and less than 1,200 nm away from the surface of the solid electrolyte in a direction from the surface of the solid electrolyte toward the center. The solid electrolyte according to claim 1 , wherein the average particle size is in the range of 2 μm to 10 μm.
8. A method for preparing a solid electrolyte, the method comprising the steps of heat treating sulfide solid electrolyte particles in the presence of ammonium fluoride in an inert gas atmosphere, Wherein, based on 100 parts by weight of the sulfide-based solid electrolyte particles, the amount of ammonium fluoride is 1 part by weight to 10 parts by weight. 9 . The method according to claim 8 , wherein the sulfide-based solid electrolyte particles are argyrodite-type solid electrolytes.
10. The method according to claim 8, wherein the heat treatment is performed by sequentially performing a first heat treatment step and a second heat treatment step, wherein the first heat treatment step is performed at a temperature of 200°C to 300°C for 1 hour to 5 hours, and The second heat treatment step is performed at a temperature of 400° C. to 600° C. for 5 hours to 10 hours.
11. An all-solid-state battery, comprising: positive electrode; a negative electrode; and The solid electrolyte according to claim 1.
Citation Information
Patent Citations
Sulfide solid electrolyte, fabrication method thereof, and all-solid-state battery comprising the same
KR1020170050562A
Billiard ball marker
KR1020220142618A
Cited By
Sulfide solid electrolyte with stable wet air, preparation method thereof and battery
CN121172237A